Antibacterial Activity of Aloe Vera Gel-based Edible Coating with the addition of Gum Arabic and Ascorbic Acid - Ni Made Defy Janurianti; I Made Supartha Utama; Ida Bagus Wayan Gunam (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2021)
Aloe vera gel has antibacterial properties. The content of antibacterial compounds in aloe vera gel is saponins, anthraquinones, tannins, aloin, and acemannan. Aloe vera gel has the potential as an edible coating for food products. The Processing carried out goes through a heating process that does think to damage the antibacterial compounds in the aloe vera gel. This study aims to determine the antibacterial activity of aloe vera gel formulated as an edible coating on S. aureus, S. mutans, E. coli and K. pneumoniae bacteria. The research method used is the disc diffusion method. Based on the test results, pure aloe vera gel has a larger inhibition zone diameter than aloe vera gel processed into an edible coating. Diameter of pure aloe vera gel inhibition zone in S. aureus, S. mutans, E. coli, and K. pneumoniae bacteria. respectively 10.966 ± 0.573 mm; 11.806 ± 0.215 mm; 10,860 ± 0.675 mm, and 10.686 ± 0.081 mm. Aloe vera gel formulated into an edible coating with antibacterial ability, namely at a concentration of 100%, which has anti activity with the inhibition zone's diameter in S. aureus, S. mutans E. coli, and K. pneumoniae bacteria, respectively. is 10,470 ± 0.213 mm; 10,673 ± 0.127 mm; 10,113 ± 0.040 mm, and 9.676 ± 0.604 mm.